SOCIAL MEDIA AS AN EFFECTIVE TOURISM MARKETING IN THE DIGITAL ERA - et. al, Siti Zakiah (International Journal of Advanced Science and Technology, 2020)
Abstract : Tourism holds great potential to be developed, including by Indonesia, which is known for its cultural and natural tourism destinations. In optimizing the potential of Indonesian tourism, one must have the right strategy. One of the keys in encouraging the increase of the number of visits while building a tourism brand that has advantages is effective management of the marketing mix including in developing appropriate promotional strategies for the sustainability of tourism destinations. The development of technology and information has pushed practices to manage the marketing mix such as promotion to be more effective. One form of promotions that can be realized and can reach broad market groups is through social media that can be a means of promoting a tourism destination. The purpose of this study includes 1) produce an overview of the profile of internet users in Indonesia, 2) produce an analysis of tourist behavior in accessing social media as a means of disseminating information and promoting tourism products, and 3) produce an analysis of the effectiveness of information dissemination and promotion through social media. The research method used is descriptive qualitative method, where researchers will describe all the things related to the use of social media as an effective tourism marketing. The results showed that social media is used in almost all ages and social media can be used as an effective means of promotion and rapid dissemination of information.